2006
DOI: 10.1603/0022-0493-99.4.1152
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Dispersal and Overwintering Habitats of Boll Weevils (Coleoptera: Curculionidae) During and After Harvest in the Subtropics

Abstract: Field experiments in the subtropical Lower Rio Grande Valley of Texas were conducted to determine the extent of adult boll weevil, Anthonomus grandis grandis Boheman (Coleoptera: Curculionidae), dispersal from cotton, Gossypium hirsutum L., fields during harvest operations and the noncotton-growing ("overwinter") period between 1 September and 1 February. Using unbaited large capacity boll weevil traps placed at intervals extending outward from commercial field edges, boll weevils did not move in substantial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…At the end of the season, when stalk destruction is mandatory, adult boll weevils leave the cotton field, moving to surrounding crop fields and native vegetation (Rummel and Adkisson, 1970;Slosser and Boring, 1980;Showler, 2006;Ribeiro et al, 2010). This dispersal activity not only assembles an adult population in the refuge area that may survive the intercropping period, but it may also explain the high capture of weevils in tubes and traps at the season end during harvesting and stalk destruction.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the season, when stalk destruction is mandatory, adult boll weevils leave the cotton field, moving to surrounding crop fields and native vegetation (Rummel and Adkisson, 1970;Slosser and Boring, 1980;Showler, 2006;Ribeiro et al, 2010). This dispersal activity not only assembles an adult population in the refuge area that may survive the intercropping period, but it may also explain the high capture of weevils in tubes and traps at the season end during harvesting and stalk destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Boll weevils have long been assumed to feed solely on pollen of certain malvaceous plants (Burke & Earle, 1965;Cate & Skinner, 1978), and later, pollens of other plants were recognized (Jones et al, 1992(Jones et al, , 1993Hardee et al, 1999), but recent research has revealed that adult boll weevils can consume cotton leaves and bracts, citrus and cactus fruit, and likely nectar (Showler & Abrigo, 2007;Showler, 2009b). In the subtropics, adult boll weevils can survive and reproduce during the winter on small patches of volunteer cotton that, despite surveillance, are overlooked, and adults can be trapped in substantial numbers around grapefruit, Citrus paradisi Macfad., and orange, C. sinensis (L.) Osbeck., orchards (Showler, 2006b). The edible endocarps of grapefruits and oranges of those citrus species can sustain up to 25% of adult boll weevils in nonreproductive condition for longer than five months (completing the cotton-free period); the maximum longevity (246 days) was only seven days less than boll weevils fed large cotton squares (Showler & Abrigo, 2007).…”
Section: Misunderstandingsmentioning
confidence: 99%
“…and other host plants in Mexico and south Texas (Gaines, 1935;Lukefahr, 1956;Lukefahr & Martin, 1962;Stoner, 1968;Cross et al, 1975;Vigueras & Portillo, 2001), cotton in the Lower Rio Grande Valley remained free of boll weevils for 30 years of commercial production beginning 1860 (Garza & Long, 2001) even though cotton around Monclova, Coahuila, Mexico, 45 minutes latitude north and 220 km west of the Lower Rio Grande Valley, was so heavily infested that the crop was abandoned in 1862 (Howard, 1897). Boll weevil food sources under orchard conditions are concentrated and support substantial active populations through winter (Showler, 2006b) because endocarps are accessible through cracks, holes, or lesions while the fruit is attached to the plant or fallen (Showler, 2007;Showler & Abrigo, 2007). Establishment of boll weevils in Lower Rio Grande Valley cotton during the early 1890s (Parencia, 1978;Haney, 2001) may have been connected to a simultaneous citrus industry boom (Waibel, 1953).…”
Section: Misunderstandingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some researchers have reported that an adult boll weevil diet of bolls elicits diapause (Lewis et al, 2002) for overwintering, the insect has not been reported to diapause in its native tropical and subtropical habitats (Guerra et al, 1984;Showler, 2007). Instead, boll weevils in the subtropical Lower Rio Grande Valley of Texas can be collected in pheromone traps year-round (Guerra et al, , 1986Showler, 2006). In the subtropics and tropics, there are alternative sources of food that can sustain boll weevils in the absence of cotton (Cross et al, 1975;Benedict et al, 1991;Jones et al, 1992;Hardee et al, 1999) including the flesh of prickly pear cactus, Opuntia spec.…”
Section: Introductionmentioning
confidence: 99%